Tehokkuus ja työhyvinvointi: Tiedolla kohti tasapainoista työtä - Tero Kuusi; Martti Kulvik; Mikko Härmä; Annina Ropponen (The Research Institute of the Finnish Economy (ETLA), 2023)
– This project investigated how register data on daily working hours and hospital patients can be used to measure the workload of healthcare personnel and to study its relationship with different work features. We used econometric analysis to measure the average labor requirement of different patient mixes in hospital wards. The data was used to analyze the overall difficulty of working days and it was then compared to the available nursing workforce. Finally, we assessed the effects of variation in the workload on well-being at work. We found that the variation in workload was related to surprising changes in work and in the availability of employees. The risk of short sick leave increased over the next week due to the high workload. We also examined the interactions between workload and the working time features for work shift planning.
Keywords: J28; I11; J45; M50; 330; Health care; Workload; Efficiency; Working time features; Occupational health